A review of the Callogobius (Teleostei: Gobiidae) from the Red Sea with the description of a new species - Delventhal, Naomi R.; Mooi, Randall D.; Bogorodsky, Sergey V.; Mal, Ahmad O. (Zootaxa, 2016)
Five species of Callogobius Bleeker have been previously reported from the Red Sea: C. amikami Goren, Miroz & Baranes, C. clarki (Goren), C. dori Goren, C. flavobrunneus (Smith), and C. maculipinnis (Fowler). Records of C. bifasciatus (Smith) in the Red Sea are referable to C. clarki. Callogobius amikami has been previously known only from a single specimen, the holotype from the Red Sea, and two photographs, a live juvenile from Oman and a live specimen at an aquarium at Coral World, Eilat. We obtained a possible additional juvenile from the Red Sea, although we are unable to definitively determine its identity. Red Sea specimens previously identified as C. maculipinnis [or C. irrasus (Smith)] represent a new species, distinguished from the latter by normally having four sets of transverse mandibular rows on each side (rather than three); this species is described here as Callogobius pilosimentum sp. nov. Four specimens of an additional, undescribed species of Callogobius, C. sp. A, have been collected from the Red Sea, but we withhold a formal description because this species is currently under study by colleagues. Callogobius sclateri (Steindachner), previously known from the Indo-West Pacific, is reported from the Red Sea for the first time. A key to all seven species is provided. Each species is photographed, habitat is described and a brief description with detailed comparisons is provided. The new species and C. clarki are endemic to the Red Sea.